2014
DOI: 10.1371/journal.pbio.1001759
|View full text |Cite
|
Sign up to set email alerts
|

Direct Type I IFN but Not MDA5/TLR3 Activation of Dendritic Cells Is Required for Maturation and Metabolic Shift to Glycolysis after Poly IC Stimulation

Abstract: Type I IFN signaling is indispensable for the maturation of dendritic cells (DCs) that are required to elicit an immune response, and it also controls a shift in cellular metabolism to meet the increased energy demands of DC maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
180
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(195 citation statements)
references
References 44 publications
(54 reference statements)
10
180
3
1
Order By: Relevance
“…The adaptation of DCs to changing metabolic states resulted from a mechanism of "metabolic checkpoint," an active signaling process involved in sensing metabolic alteration and subsequently signaling transaction and execution (56). Recent studies indicated that a Tolllike receptor signaling-mediated metabolic reprogramming is required for DC maturation and antigen presentation (57)(58)(59). Moreover, the dysregulated mTORC1 or the adenosine monophosphate (AMP)-activated protein kinase (AMPK) activity results in an impaired DC development and maturation, indicating a metabolic checkpoint sensing amino acids and intracellular ATP during DC development and maturation (58,60).…”
Section: Discussionmentioning
confidence: 99%
“…The adaptation of DCs to changing metabolic states resulted from a mechanism of "metabolic checkpoint," an active signaling process involved in sensing metabolic alteration and subsequently signaling transaction and execution (56). Recent studies indicated that a Tolllike receptor signaling-mediated metabolic reprogramming is required for DC maturation and antigen presentation (57)(58)(59). Moreover, the dysregulated mTORC1 or the adenosine monophosphate (AMP)-activated protein kinase (AMPK) activity results in an impaired DC development and maturation, indicating a metabolic checkpoint sensing amino acids and intracellular ATP during DC development and maturation (58,60).…”
Section: Discussionmentioning
confidence: 99%
“…The glycolytic metabolism is known to regulate cytokine expression in activated immune cells (29)(30)(31)(32), as IL-6 expression in murine monocytic cell lines is lowered upon downregulation of the glycolytic pathway by 2-deoxyglucose (33), TNF-a is downregulated by lactate (34), and IL-1b expression is enhanced by a TLR-dependent stabilization of HIF-1a (35), a process further enhanced by succinate accumulation (36). Our data show that IL6, IL1B, and TNF mRNA are positively regulated by the glycolytic pathway in proinflammatory GM-MØ; whereas a drop of GM-MØ ECAR levels correlates with reduced IL6, IL1B, and TNF mRNA levels, inhibition of mitochondrial respiration leaves the expression of these cytokine genes unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that mouse classical DCs do not express Nos2, they do exhibit diminished mitochondrial activity and enhanced glycolysis over the long term after activation with TLR agonists in vivo. These changes are reported to be driven by autocrine type I interferon signaling through HIF-1α (Pantel et al, 2014).…”
Section: Switching To Warburg Metabolism Allows Cellular Activation Amentioning
confidence: 99%
“…Despite the fact that mouse classical DCs do not express Nos2, they do exhibit diminished mitochondrial activity and enhanced glycolysis over the long term after activation with TLR agonists in vivo. These changes are reported to be driven by autocrine type I interferon signaling through HIF-1α (Pantel et al, 2014).Core nutrient/energy-sensing pathways in metabolic reprogramming in DCs Cells possess central signaling pathways that are able to sense nutrient and/or energy status and adjust metabolism to be anabolic or catabolic as required. Cellular growth requires anabolic metabolism, and this can be regulated by mTORC1 downstream of PI3K/Akt and growth factor receptors (Fig.…”
mentioning
confidence: 99%